The Influence Of Parenting Mindfulness On Parenting Stress In Parent Unions Children With Down Syndrome(POTADS), Padang - Yorike, Viony - (Psibernetika, 2023)
AbstractProblems and limitations in Down Syndrome children can causes parenting stress for parents in parenting. To minimize the impact of parenting stress, a strategy is needed to overcome it, one of that is mindfulness parenting. The purpose of this study is to determine the effect between mindfulness parenting and parenting stress in parents who have children whith Down Syndrome at Parents Unions with Down Syndrome (POTADS), Padang. This study used a quantitative research method with simple linear regression analysis technique. This study was conducted with 60 parents of children with Down Syndrome in  Parents Unions with Down Syndrome (POTADS), Padang using total population sampling technique. Data was collected using the adaptation of the Mindfulness in Parenting Questionnaire (MIPQ) and Parenting Stress Scale (PSS). The result of this study showed that Mindfulness Parenting has a significant effect on Parenting Stress parents of children with Down Syndrome in  Parents Unions with Down Syndrome (POTADS), Padang. It can be seen from the significance value which is .00 (p<.05). The R2 value was .205, which means that mindfulness parenting effect parenting stress parents of children with Down Syndrome in  Parents Unions with Down Syndrome (POTADS), Padang by 20.5%.Keywords: Parenting stress, mindfulness parenting, parents of children with down syndrome in POTADS